Statins inhibit in vitro virulence phenotypes of Pseudomonas aeruginosa - Hennessey, E.; Mooij, M.; Legendre, C.; Reen, F.; O'Callaghan, J.; Adams, C.; O'Gara, Fergal (Nature Publishing Group, 2013)
Statins are a family of drugs that lower cholesterol levels by inhibiting 3-hydroxy-3-methylglutaryl-CoA-reductase, a rate-limiting enzyme in the human mevalonate pathway of which cholesterol is the biosynthetic end product.1 Statins also have a range of cholesterol-independent effects, including anti-inflammatory functions and antimicrobial activity. These pleiotropic effects are thought to account for the improved survival observed in statin-treated patients suffering from severe bacterial infections, such as sepsis and pneumonia. In order to identify the mechanism involved in the protective effects of statins against infection, research studies focused on the direct effect of statins on bacteria.